2016
DOI: 10.1177/0003702816654149
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Spectroscopy and Photoacoustic Spectroscopy for Saliva Analysis

Abstract: Saliva provides a valuable tool for assessing oral and systemic diseases, but concentrations of salivary components are very small, calling the need for precise analysis methods. In this work, Fourier transform infrared (FT-IR) spectroscopy using transmission and photoacoustic (PA) modes were compared for quantitative analysis of saliva. The performance of these techniques was compared with a calibration series. The linearity of spectrum output was verified by using albumin-thiocyanate (SCN(-)) solution at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Preliminary analysis of the data obtained by FTIR demonstrated that the spectra of all samples within a certain experimental group involved one and the same set of vibration modes. The use of FTIR for the analysis qualitatively demonstrated that the molecular composition of the mixed saliva was characterised by a specific set of vibration modes in the IR spectra, in agreement with published data on biological fluids [21,[27][28][29][30][31].…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Preliminary analysis of the data obtained by FTIR demonstrated that the spectra of all samples within a certain experimental group involved one and the same set of vibration modes. The use of FTIR for the analysis qualitatively demonstrated that the molecular composition of the mixed saliva was characterised by a specific set of vibration modes in the IR spectra, in agreement with published data on biological fluids [21,[27][28][29][30][31].…”
Section: Resultssupporting
confidence: 84%
“…The most intensive vibration in this group of bands is a mode in the range of 2150-1950 cm −1 . According to the data of [29], this mode is related to the −N=C=S bond of thiocyanate anions that are present in mixed saliva. Visual analysis of the intensity for this vibration in the spectrum of the oral fluid obtained from those with multiple caries demonstrated that it is considerably more intensive than for the healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations